2017
DOI: 10.3847/1538-4357/aa79a6
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-induced Collapse from Helium Star + White Dwarf Binaries

Abstract: Accretion-induced collapse (AIC) occurs when an O/Ne white dwarf (WD) grows to nearly the Chandrasekhar mass (M Ch ), reaching central densities that trigger electron captures in the core. Using Modules for Experiments in Stellar Astrophysics (MESA), we present the first true binary simulations of He star + O/Ne WD binaries, focusing on a 1.5M He star in a 3 hour orbital period with 1.1−1.3M O/Ne WDs. The helium star fills its Roche lobe after core helium burning is completed and donates helium on its thermal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…But this presumably converts the entire C/O core into O/Ne (Nomoto & Iben 1985;Lecoanet et al 2016). For an initially O/Ne core, this flame converts the C/O shell to O/Ne (Brooks et al 2017).…”
Section: Mesa Modelsmentioning
confidence: 99%
“…But this presumably converts the entire C/O core into O/Ne (Nomoto & Iben 1985;Lecoanet et al 2016). For an initially O/Ne core, this flame converts the C/O shell to O/Ne (Brooks et al 2017).…”
Section: Mesa Modelsmentioning
confidence: 99%
“…Brooks et al (2016) calculated full binary evolution of WD+He star systems, whereas we suppose that off-centre carbon burning occurs if the mass-transfer rate is higher thanṀcr. Note that the results obtained here are very similar to those of Brooks et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum delay time in Figure 4 is determined by the MS lifetime of a 8 M ⊙ star, which is the maximum mass of a star able to form CO WDs. Brooks et al (2016) recently also reported these two possible outcomes (i.e., centre or off-centre carbon ignition), but they calculated over a narrower range of parameter space.…”
Section: Birthrates Of Sne Iamentioning
confidence: 99%
See 1 more Smart Citation
“…This mild expansion is not enough to power mass loss, but is enough to temporarily prevent surface accretion. This can be seen in Figure 4, which shows the mass transfer rate by the dotted black line and the WD mass accretion rate by the solid black line, which has sharp dips caused by the carbon burning flashes (Brooks et al 2017).…”
Section: Wd Companionmentioning
confidence: 90%